Epidemiology and Clinical Patterns of Leprosy: A Retrospective Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Ariani, Tutty; Triani , Aisha; Aulia , Salsabila Syafna (Frontiers on Healthcare Research, 2025)
Background: Indonesia ranks third globally in the number of leprosy cases, following Brazil and India. Despite this, leprosy remains a neglected disease. Monitoring its epidemiology through retrospective studies is essential to inform effective disease control programs. Methods: This retrospective descriptive study reviewed medical records of leprosy patients who visited Dr. M. Djamil General Hospital, Padang, between 2021 and mid-2024. Data were extracted from patients’ electronic medical records. Results: A total of 92 patients were confirmed with leprosy during the study period. The incidence increased from 13 patients in 2021 to 22 in 2022, and 40 in 2023, with 17 additional cases identified by mid-2024. Of these, 70 (76.1%) were multibacillary cases and 22 (23.9%) were paucibacillary cases. Male patients predominated, with a mean age of 35 years (range: 7–79 years). Leprosy reactions occurred in 44 patients (47.8%), consisting of 20 (45.5%) reversal reactions and 24 (54.5%) erythema nodosum leprosum (ENL). Most cases originated from Pesisir Selatan Regency and Pariaman City, both recognized as high-endemic areas in West Sumatra Province. Conclusion: The incidence of leprosy is rising annually, with multibacillary cases predominating. Male patients are more frequently affected, and nearly half experience leprosy reactions, with ENL more common than reversal reactions. Strengthened disease control strategies are urgently needed to detect and reduce new cases in endemic regions. Study limitations include reliance on retrospective medical record data and a single tertiary hospital setting.